The effect of temperature on the chromizing process for Ferritic-Martensitic steel - F, Farah Alia; Kurniawan, Tedi; Ani, Mohd Hanafi; Nandiyanto, Asep Bayu Dani (IOP Publishing, 2017)
The formation of protective Cr2O3 layer was usually retarded in the high temperature steam oxidation of boiler tube materials. This condition makes the oxidation rate higher than that in dry condition. Therefore in this work, chromizing process is introduced to diffuse chromium on the surface of boiler steel so that it can act as a reservoir for the formation of Cr2O3 layer. The chromizing process was conducted on T91 steel by exposing it into alumina crucible. The crucible was exposed at different temperature (600oC-1050oC) under argon environment in the crucible that contains the chromizing mixture powder of masteralloy Cr, activator NH4Cl and filler Al2O3. It was found that Cr diffusion was happened at higher temperature and it formed Cr carbide on the surface. It also clarified that this chromizing process can prevent the retardation of Cr2O3 layer.